Istrian and Dalmatian towns - urban space and the elites : the cases of Rovinj and Rab (Middle Ages and Early Modern Period) - Mlacović, Dušan (Array, 2019)
The authors focus on the issue of urban elites in two Adriatic cities, Rab and Rovinj, which differ in their origins and development alike. Rab is an ancient civitas, while Rovinj was classified as a terra in the Venetian administrative system. The two cities also differ in the amount of their preserved written sources. Whereas the medieval sources for Rovinj are only sporadic, for Rab there are a number of notarial books from the late Middle Ages, which allows for a different approach to the spatial identification of urban elites than in Rovinj’s case. Based on the available sources, the paper compares the development, significance, and status of urban elites in both cities